The landing gear case study: challenges and experiments - Boniol, Frédéric; Wiels, Virginie; Aït-Ameur, Yamine; Schewe, Klaus-Dieter (International journal on software tools for technology transfer, 2017)
Embedded critical systems need to be validated very thoroughly; it usually results in very long and onerous test phases. Formal techniques, in particular formal specification languages and associated proof tools, could be an advantageous alternative, or at least a good complement and allow a significant reduction of test phases. However, for these techniques to be used in practice, one issue to consider is their efficiency and scalability on complex industrial systems.Case studies have played an essential role in the history of formal methods. They have allowed to illustrate the application of formal techniques for modelling and verification, to compare different methods in terms of expressivity, performance and easiness of use. They have also permitted to enact the progress made by these methods.Dagstuhl seminar 9523 is about the famous Steam Boiler case study in 1995 had a lot of impact on the formal methods community. This case study allowed the assessment of formal techniques, the comparison of different formal techniques, the identification of areas for future work.